An analysis of exogenous harmful substance exposure as risk factors for COPD and hypertension co-morbidity using PSM - Chen, Qingyang; Zhou, Haodong; Tang, Jiarong; Sun, Yingbiao; Ao, Geriletu; Zhao, Hongjun; Chang, Xuhong (Frontiers in Public Health, 2024)
Background: Some occupational and environmental exposures could increase the risk of COPD and hypertension under different working or living environment. However, it was unclear for the effect between multiple exogenous harmful substances exposure and COPD and hypertension comorbidities. Methods: Participants were selected from eight hospitals in five provinces of China using a multistage cluster sampling procedure. Participants' demographic, exposure, and disease information were collected through questionnaires and spirometry and blood pressure examinations. Demographic data were used as matching factors, and 1:1 matching between exposed and nonexposed groups was performed by using Propensity Score Matching (PSM) to minimize the influence on the results. One-way chi-square analysis and multifactorial logistic regression were used to analyze the association between exogenous harmful substances exposure (metals and their compound dusts, inorganic mineral dusts, organic chemicals, and livestock byproducts) and the co-morbidity of COPD and hypertension. Results: There were 6,610 eligible participants in the final analysis, of whom 2,045 (30.9%) were exposed to exogenous harmful substances. The prevalence of comorbidities of COPD and hypertension (6.0%) in exposure group was higher than the prevalence of the total population (4.6%). After PSM, exogenous harmful substances exposure was found as a risk factor for co-morbidity of COPD and hypertension (OR=1.347, 95%CI 1.011-1.794), which has showed not statistically significant before PSM (OR=1.094, 95%CI 0.852-1.405). Meanwhile result of different outcomes showed that the association between hypertension and exogenous harmful substances exposure was not statistically significant (OR=0.965, 95%CI 0.846-1.101). Smoking (OR=4.702, 95%CI 3.321-6.656), having respiratory disease during childhood (OR=2.830, 95%CI 1.600-5.006) and History of respiratory symptoms (OR=1.897, 95%CI 1.331-2.704) were also found as risk factors for co-morbidity of COPD and hypertension. Conclusion: The distribution of exogenous harmful substance exposures varies in the population, and the prevalence of comorbidities is generally higher in susceptible populations. Exposure to exogenous harmful substances was found to be a key risk factor after balancing demographic confounders.